STRENGTH ANALYSIS OF THE INTERMEDIATE SHAFT AND THE CAGE OF CONSTANT VELOCITY UNIVERSAL JOINT TRANSMISSION ASSEMBLY FOR A HEAVY⁃DUTY VEHICLE - SONG YouShuo; MIAO JiaJun; LU Xi (Jixie qiangdu)
The force and torque transmitted by the ball cage constant velocity universal joint transmission assembly of heavy⁃duty vehicles are greater than that of ordinary vehicles,and the working conditions have higher requirements.Under the impact load,static strength failure or fatigue failure of the intermediate shaft may occur,as well as the cage damage under the bigger interaxial angles.Therefore,it is very important to study the strength of the intermediate shaft and the cage in the ultimate working condition.In this study,the ball cage constant velocity universal joint transmission assembly for a heavy⁃duty vehicle was taken as the object.Firstly,the force analysis and the finite element simulation were carried out on the intermediate shaft and the results were compared to verify the model accuracy.Secondly,the stress distribution and variation law of the cage were obtained through simulation analysis under the different interaxial angles.Finally,the torsional static strength test and the cage hardness test were carried out.The results show that the intermediate shaft and the cage meet the requirements under normal working conditions,but the cage may be broken under extreme working conditions.This research can provide reference for the design and manufacture of ball cage constant velocity universal joint transmission assembly of heavy⁃duty vehicles.